International directory of company histories. Volume 174. - Long, Steven; Jacques, Derek; Kepos, Paula; Gale Group (Farmington Hills, Mich. St. James Press, a part of Gale, Cengage Learning, 2016)
Provides histories of companies that are a leading influence in a particular industry or geographic location. For students, job candidates, business executives, historians and investors.
Access National Corporation -- Aegion Corporation -- Allied Motion Technologies, Inc. -- American Woodmark Corporation -- Angels Baseball LP -- API Technologies Corp. -- Apple Corps Ltd. -- Ark Restaurants Corp. -- Atlanta National League Baseball Club, Inc. -- AV Homes, Inc. -- Bank of South Caroline Corporation -- Bergdorf Goodman, Inc. -- Brooks Sports Inc. -- BSCV Department Store, LLC -- Calkins Media Incorporated -- Canada Post Corporation -- Carahsoft Technology Corporation -- Carlson Wagonlit Travel, Inc. -- Case Foods, Inc. -- The Children's Place, Inc. -- China Film Group Corporation -- Citizens Financial Group, Inc. -- Clipper Magazine, LLC -- Columbus McKinnon Corporation -- ConAgra Foods, Inc. -- CotterWeb Enterprises, Inc. -- DCM Ventures -- Dechert LLP -- Des Moines Register and Tribune Company -- Dyckerhoff GmbH -- Edelbrock, LLC -- El Corte Ingles Group -- Envigo -- EVINE Live Inc. -- Finolex Industries Ltd. -- Forbes Media -- Gazprom OAO -- Granite Broadcasting Corporation -- H&S Bakery, Inc. -- Hardaway Construction Corporation -- Hardinge Inc. -- Harlequin Enterprises Limited -- J.B. Poindexter & Co. Inc. -- John W. Danforth Company -- Kona Brewing Company, Inc. -- Korea International Broadcasting Foundation -- Lake Sunapee Bank Group -- Manischewitz Company, Inc. -- Match Group, LLC -- Meade Instruments Corp. -- Medallion Financial Corporation -- Medicine Man Production Corporation -- Mexican Restaurants, Inc. -- MOCON Inc. -- Morton Salt, Inc. -- Murree Brewery Company Limited -- Mustad International Group B.V. -- Nowy Styl Group -- Ocean Choice International, Inc. -- The ONE Group Hospitality, Inc. -- Oregon Shakespeare Festival Association -- Pathe -- Peace Dining Corporation -- Peak Resorts, Inc. -- Perfetti Van Melle SpA -- Pierce Manufacturing Inc. -- Planet Payment, Inc. -- PMFG Inc. -- Point Roll, Inc. -- Prasar Bharati Broadcasting Corporation -- Prodrive Ltd. -- Ragdoll Productions Ltd. -- Ralphs Grocery Company -- Red Hot & Blue Restaurants, Inc. -- Richardson Electronics, Ltd. -- Rieter Group -- San Jose Mercury News, Inc. -- Schneider National, Inc. -- Seaboard Corporation -- Smith & Wesson Corp. -- Sotheby's -- Sotherly Hotels Inc. -- South Jersey Industries, Inc. -- Spirit Airlines, Inc. -- Stolt-Nielsen Ltd. -- Stryker Corporation -- Swift Transportation Corporation -- Taco Bueno Restaurants, L.P. -- Towerstream Corporation -- United Natural Foods, Inc. -- Vacasa, LLC -- Vente-Privee.com S.A. -- Village Super Market, Inc. -- Wadia Group -- Walton Isaacson, LLC -- Webb Wheel Products, Inc. -- The Weitz Company, LLC -- Wells Lamont LLC -- The York Water Company.
Includes bibliographical references and indexes.
Keywords: Big business -- History -- Directories; Business enterprises -- History -- Directories; Corporations -- History -- Directories